1985
DOI: 10.1177/33.10.3900197
|View full text |Cite
|
Sign up to set email alerts
|

Human cytotrophoblast populations studied by monoclonal antibodies using single and double biotin-avidin-peroxidase immunocytochemistry.

Abstract: Single and double biotin-avidin-peroxidase immunocytochemical methods in conjunction with an anti-trophoblast monoclonal antibody 18B/A5 and an anti-HLA-A,B,C monoclonal antibody W6/32 were used to study various human trophoblast populations. Several combinations of peroxidase substrates were tried in the double-labeling procedure. It was concluded that the use of 4-chloro-1 naphthol to develop the primary sequence peroxidase and of 3-amino-9-ethyl carbazole for the second sequence peroxidase was the most suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Our findings are the first to show that MHC class II molecules can be induced by a CIITA-independent mechanism under pathological conditions in vivo: corneal allograft rejection and cuprizone-induced demyelination of the brain. It has also been shown that MHC class II is expressed on aborted placentas [31,32]. These results indicate that a CIITA-independent pathway to MHC class II expression exists within cells of certain immune-privileged tissues (cornea, brain, placenta) and that expression of MHC class II under these conditions may have immunopathogenic consequences.…”
Section: Discussionmentioning
confidence: 65%
“…Our findings are the first to show that MHC class II molecules can be induced by a CIITA-independent mechanism under pathological conditions in vivo: corneal allograft rejection and cuprizone-induced demyelination of the brain. It has also been shown that MHC class II is expressed on aborted placentas [31,32]. These results indicate that a CIITA-independent pathway to MHC class II expression exists within cells of certain immune-privileged tissues (cornea, brain, placenta) and that expression of MHC class II under these conditions may have immunopathogenic consequences.…”
Section: Discussionmentioning
confidence: 65%
“…Acetone/methanolfixed cells were allowed to react with anti-cytotrophoblast monoclonal antibody 18B/A5 (kindly provided by Y. W. Loke, Univ. of Cambridge) (7). Avidin-biotin-peroxidase (Vectastain, Burlingame, CA) and 0.05% diaminobenzidine (Sigma) were used to localize bound antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Other published methods such as microwaving in citrate buffer and enzymatic precipitation of the substrates as a shielding technique (Butterworth et al 1985;Sternberger and Sternberger 1986;Lewis Carl et al 1993;Lan et al 1995;Tornehave et al 2000) were also compared with the present procedure and were found less efficient, mainly because of their increased tendency of damaging the tissue, the appearance of more sensitive detection methods, or too laborious optimizations. In another recently published method, primary antibodies were non-covalently labeled in vitro with monovalent Fab fragments carrying the reporter molecules (Brown et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…After elution, the slides were washed abundantly in PBS-Tween and processed for the next immunodetection procedure. In addition, we also chose to compare other methods such as microwaving in citrate buffer to test the efficiency of enzymatic precipitation of the substrates as an antibody shielding procedure (Butterworth et al 1985;Sternberger and Sternberger 1986;Lewis Carl et al 1993;Lan et al 1995;Tornehave et al 2000;Toth and Mezey 2007).…”
Section: Antibody Elution Techniquesmentioning
confidence: 99%
See 1 more Smart Citation